ANALISIS KELAYAKAN USAHA TERNAK KAMBING MANDIRI FARM DI KABUPATEN MIMIKA - Marfiati Yamco; Maria Irma Renmeuw; Tri Apriyono (CV. Adiba Aisha Amira, 2023)
This research aims to determine the feasibility level of goat farming in Mimika Regency from a financial and non-financial perspective. To achieve this goal, the research method used is a descriptive research method. In this research, the data collection techniques used were observation, interviews and documentation techniques. To determine the feasibility level of the Mandiri Farm goat farming business in Mimika Regency, the analytical instruments used in this research are financial aspect analysis using (B/C Ratio) and analysis of technical and technological aspects, marketing aspects, environmental aspects, and legal aspects using using source triangulation analysis. The results of this research show that the goat farm managed by the owner of the Mandiri Farm goat farm is said to be feasible from the financial and marketing aspects, technical and technological aspects, and not yet feasible from the environmental and legal aspects.